Tuberculous peritonitis: an analysis of case series of 49 consecutive patients - Büyükkurt, Elif; Yılmaz, Ömer; Albayrak, Bulent; Bilge Yerli, Ezel (The European Research Journal, 2024)
Objectives: The incidence of tuberculous peritonitis has been reported between 0.1% and 0.7% among all tuberculosis types. This study, it was aimed to evaluate the cases with tuberculous peritonitis, which has an important place in the differential diagnosis of patients with ascites, clinically, biochemically, microbiologically, and histopathologically. Methods: : Forty-nine patients with a definite clinical, radiological, and histopathological diagnosis of tuberculous peritonitis, which formed the basis of our study, were analyzed retrospectively. Results: The mean age of patients with tuberculous peritonitis was found to be 39.45 ± 19.02 years. Purified-protein derivative (PPD) was positive in 23 (72%) of 32 patients with tuberculous peritonitis whose PPD results were recorded, in 9 (28%) PPD results were evaluated as anergic or negative. QuantiFERON-TB Gold In-Tube (QFT-GIT) test was sent in 10 of the patients, the result was positive in 9 (90%) patients and negative in 1 (10%) patient. There were 32 patients in whom tuberculosis polymerase chain reaction (PCR) was studied from ascitic fluid, 7 (22%) of the patients were PCR positive and 25 (78%) negative. Mycobacterium tuberculosis culture positivity was found in 18 (69%) of 26 patients who were biopsied. In total, 29 (59%) of the patients had M. tuberculosis culture positivity. Conclusions: Tuberculous peritonitis constitutes a public health problem in endemic regions of the world and tuberculous peritonitis should be considered in patients presenting with ascites. Despite all diagnostic difficulties, necessary tests, especially peritoneal biopsy, should be performed for early diagnosis, and it should not be forgotten that early initiation of treatment is very important in terms of morbidity and mortality of the disease.